When Teacher’s Beliefs and Student’s Self-esteem Are in Conflict: A Case for Including Social Metacognition in Teacher Education Curriculum - P. Bhaskaran Nair (An Overview of Literature, Language and Education Research Vol. 2, 2024)
Social metacognition is a blend of sociology, psychology and cognition. One area that this branch of study investigates is the matches and mismatches between one’s assessment of oneself and the assessment by others in a social context. The pedagogical potentials of social metacognition form the core of this paper. Though not based on any empirical study, the conclusions arrived at in this study are mainly drawn from long-time observations of the changes in the behavioural patterns of school children. As the title suggests, this paper attempts to juxtapose these two fundamental concepts underlying the success (or failure) of teaching. Culturally absorbed professional behaviours such as teacher entitlement and teacher belief most often function in antithesis to children’s genetically acquired self-esteem. Judgments have been cited as the main component of cognition by psychologists. We judge ourselves and we are constantly being judged by others. In these simultaneously occurring processes, the data being studied need not be the same. Even if the same, the mode of observation being subjective, judgement certainly differs; and as a result, our self-judgments need not correspond with others’ assessment about us. In a social group like a class or school, this conflict leads to irreparable relationship breakdown. This paper is an attempt to study the effect of one such mismatch between teacher beliefs and student’s self-judgment by applying certain fundamental principles of social metacognition in pedagogy.